Personal exploration: Serendipity and intentionality as altering positions in a creative process - Mäkelä, Maarit (FormAkademisk, 2016)
Artists and designers have recently begun to take an active role in contextualising the creative process in relation to their practice. Thus, understanding how the creative mind proceeds has been supplemented with knowledge obtained inside the creative process. In this way, the spheres of knowledge, material thinking and experience that are fostered through creative work have become entangled and embedded as elemental parts of the research process. This article is based on documentation and reflection of the author’s creative practice in contemporary ceramic art at the beginning of 2015. The article discusses how the creative process proceeds by alternating between two positions: serendipity and intentionality. By describing the different phases of the process, it reveals the interplay between the diverse range of activities and how these gradually construct the creative process